2021
DOI: 10.1038/s41698-021-00198-9
|View full text |Cite
|
Sign up to set email alerts
|

A DNA methylation-based liquid biopsy for triple-negative breast cancer

Abstract: Here, we present a next-generation sequencing (NGS) methylation-based blood test called methylation DETEction of Circulating Tumour DNA (mDETECT) designed for the optimal detection and monitoring of metastatic triple-negative breast cancer (TNBC). Based on a highly multiplexed targeted sequencing approach, this assay incorporates features that offer superior performance and included 53 amplicons from 47 regions. Analysis of a previously characterised cohort of women with metastatic TNBC with limited quantities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Here, we performed a head-to-head comparison between methylome analyses results derived from serum and plasma cfDNA and observed that these 2 sources of DNA are different in several aspects, such as cell composition estimations and genome-wide and supervised mean methylation levels; however, they both provided unique or common PitNET-specific markers that were able to differentiate PitNETs from other tumors, suggesting that the use of either blood element is useful, and possibly complementary, as a noninvasive methylation-based diagnostic tool ( Supplementary Figure S2C ; Supplementary File S5 ). 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…Here, we performed a head-to-head comparison between methylome analyses results derived from serum and plasma cfDNA and observed that these 2 sources of DNA are different in several aspects, such as cell composition estimations and genome-wide and supervised mean methylation levels; however, they both provided unique or common PitNET-specific markers that were able to differentiate PitNETs from other tumors, suggesting that the use of either blood element is useful, and possibly complementary, as a noninvasive methylation-based diagnostic tool ( Supplementary Figure S2C ; Supplementary File S5 ). 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…Several markers have been previously shown to be associated with BC. 9,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The protein kinase CDKL2 was reported to be hypermethylated in HER2-positive BC tissues compared to normal breast tissues. 40 Its differential methylation was associated with response to neoadjuvant chemotherapy in patients with TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study on metastatic TNBC, an AUC of 0.92 was reported using a next-generation sequencing (NGS) methylation-based blood test. 32 In another study, a DNA methylationbased epigenetic signature of breast DNA was described using three methylation markers. 43 The later study was performed on plasma samples of BC patients with metastatic and localized disease and reported an AUC of 0.9 and 0.91, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is an epigenetic modification that is associated with regulating cell differentiation and tissue development ( Smith and Meissner, 2013 ; Slieker et al, 2015 ). Dysregulation of DNA methylation patterns are important characteristics of several diseases, including cancers ( Li et al, 2013 ; Božić et al, 2021 ; Cristall et al, 2021 ; Miyakuni et al, 2021 ). 5-Methylcytosine (5mC), a type of DNA methylation, was firstly reported by Wyatt, (1951) .…”
Section: Introductionmentioning
confidence: 99%